2020
DOI: 10.1038/s41419-020-2454-8
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential ion channel TRPM2 promotes AML proliferation and survival through modulation of mitochondrial function, ROS, and autophagy

Abstract: Transient receptor potential melastatin 2 (TRPM2) ion channel has an essential function in maintaining cell survival following oxidant injury. Here, we show that TRPM2 is highly expressed in acute myeloid leukemia (AML). The role of TRPM2 in AML was studied following depletion with CRISPR/Cas9 technology in U937 cells. In in vitro experiments and in xenografts, depletion of TRPM2 in AML inhibited leukemia proliferation, and doxorubicin sensitivity was increased. Mitochondrial function including oxygen consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 58 publications
5
68
1
3
Order By: Relevance
“…Mitochondrial calcium uptake significantly improved depleted cells and regulated cytosolic calcium signal [27,28]. Our results indicated that increased Ca 2+ levels of mitochondrial significantly upregulate the expression of PGC-1, NRF-1, and mtTFA, is one of the signals mediating mitochondrial biogenesis.…”
Section: Effects Of Bupivacaine On Myocardial Mitochondrial Biogenesismentioning
confidence: 59%
“…Mitochondrial calcium uptake significantly improved depleted cells and regulated cytosolic calcium signal [27,28]. Our results indicated that increased Ca 2+ levels of mitochondrial significantly upregulate the expression of PGC-1, NRF-1, and mtTFA, is one of the signals mediating mitochondrial biogenesis.…”
Section: Effects Of Bupivacaine On Myocardial Mitochondrial Biogenesismentioning
confidence: 59%
“…Mitochondrial calcium uptake signi cantly improved depleted cells and regulated cytosolic calcium signal [27,28]. Our results indicated that increased Ca 2+ levels of mitochondrial signi cantly upregulate the expression of PGC-1, NRF-1, and mtTFA, is one of the signals mediating mitochondrial biogenesis.…”
Section: Effects Of Bupivacaine On Myocardial Mitochondrial Biogenesismentioning
confidence: 61%
“…Transient receptor potential melastatin 2 (TRPM2) belongs to non-selective cation channels. Its role in regulating cancer growth and metastasis was confirmed by many studies [129,130]. On the other hand, selective downregulation of TRPM2 via shRNA results in the proliferation decrease and apoptosis promotion in gastric and lung cancer cells.…”
Section: Anticancer Therapies Targeting Ion Channelsmentioning
confidence: 84%